THE INFLUENCE OF MANAGEMENT CONTROL SYSTEMS ACCOUNTING INFORMATION SYSTEMS AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. WASPADA DINASTI ERIASAFA - Nasution, Fadlina Raya (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to determine the Effect of Management Control System, Accounting Information System, and Work Discipline at PT. Waspada Dinasti Eriasafa. This research is a type of quantitative research. The population in this study were all employees at PT. Waspada Dinasti Eriasafa. The sampling technique in this study was Nonprobability Sampling technique using saturated sampling, which is a sampling technique when all members of the population are used as samples. The sample in this study were 32 respondents. The data collection technique in this study was carried out by distributing questionnaires to research respondents. The analysis method used in this research is multiple linear regression using the help of the SPSS version 26 program: Partially, the management control system and accounting information system have a significant effect on employee performance and work discipline has no significant effect on employee performance. Simultaneously Management Control System, Accounting Information System and Work Discipline have a significant effect on Employee Performance.